2019
DOI: 10.1080/13102818.2019.1649094
|View full text |Cite
|
Sign up to set email alerts
|

Development andin vitrosafety evaluation of pramipexole-loaded hollow mesoporous silica (HMS) particles

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Development and in vitro safety evaluation of pramipexole-loaded hollow mesoporous silica (HMS) particles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Formulation 1, referred to as the PVA-PDM formulation, consisted of 5% ( w / w ) pramipexole dihydrochloride monohydrate (PDM, Chr. Olesen, Denmark) as an API of the biopharmaceutics classification system (BCS) class I, declared as good water solubility (c s ≥ 200 mg/mL) [ 49 , 50 ]. Mannitol (Parteck M ® , Merck, Germany) was used as a plasticizer at 10% ( w / w ) content.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formulation 1, referred to as the PVA-PDM formulation, consisted of 5% ( w / w ) pramipexole dihydrochloride monohydrate (PDM, Chr. Olesen, Denmark) as an API of the biopharmaceutics classification system (BCS) class I, declared as good water solubility (c s ≥ 200 mg/mL) [ 49 , 50 ]. Mannitol (Parteck M ® , Merck, Germany) was used as a plasticizer at 10% ( w / w ) content.…”
Section: Methodsmentioning
confidence: 99%
“…baskets, except that the mesh width was changed to 3 mm. The dissolution test for PDM containing tablets was performed in 500 mL of degassed 0.1 N hydrochloric acid at pH 1.2 under sink conditions (c s ≥ 200 mg/mL [ 50 ]; maximum concentration 0.08 mg/mL) and stirred at 50 rpm at a temperature of 37 ± 0.5 °C. The released API was measured using an UV-Vis spectral photometer (UV-1800 Shimadzu, Japan) at a wavelength of 263 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity assay results suggested that the toxicity of the free drug was greatly reduced upon encapsulation in coated MSNs, and the designed drug delivery system showed promising potential in preventing H 2 O 2 -induced oxidative damage in human neuroblastoma SH-SY5Y cells [47]. The same group later demonstrated the ability of chitosan and sodium alginate coated hollow MSNs for the delivery of dopamine-receptor agonist pramipexole [68].…”
Section: Polymer Coated Msns For Neurodegenerative Diseasesmentioning
confidence: 96%
“…In vitro drug release studies have demonstrated a sustained release pattern at both intestinal and gastric pH values. In addition, no hemolysis was found for HMS-pramipexole NPs, and SH-SY5Y treatment resulted in a better antioxidant protection effect when compared with pramipexole alone [ 121 ]. In the same year, Tzankov and his team developed another type of mesoporous silica NP (MCM-41) to incorporate into pramipexole for oral administration.…”
Section: Nanoparticles As Drug Delivery System Repurposing In Pdmentioning
confidence: 99%